2014
DOI: 10.1128/jb.01469-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Glycoproteins on the Spore Surface of Clostridium difficile

Abstract: In this study, we identify a major spore surface protein, BclA, and provide evidence that this protein is glycosylated. Following extraction of the spore surface, solubilized proteins were separated by one-dimensional PAGE and stained with glycostain to reveal a reactive high-molecular-mass region of approximately 600 kDa. Tandem mass spectrometry analysis of in-gel digests showed this band to contain peptides corresponding to a putative exosporangial glycoprotein (BclA3) and identified a number of glycopeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…ClosTron-generated mutants of the bclA1 and bclA2 determinants produced spores with altered surfaces, including release of "sheets of coat-like material" from the spores (188). BclA3 was identified as a glycosylated protein in extracts of C. difficile spores, and the glycosyltransferase gene sgtA, carried upstream of bclA3, is at least partly responsible for glycosylation of the spore surface (189).…”
Section: Clostridium Difficilementioning
confidence: 99%
“…ClosTron-generated mutants of the bclA1 and bclA2 determinants produced spores with altered surfaces, including release of "sheets of coat-like material" from the spores (188). BclA3 was identified as a glycosylated protein in extracts of C. difficile spores, and the glycosyltransferase gene sgtA, carried upstream of bclA3, is at least partly responsible for glycosylation of the spore surface (189).…”
Section: Clostridium Difficilementioning
confidence: 99%
“…In the hyper-virulent strain R20291 of C. difficile the BclA proteins showed 56% similarity with the BclA protein of Bacillus anthracis [10], known to be highly immunogenic and to act as spore surface ligand for α2β1 integrin present in IECs driving spore entry into the epithelial barrier [11]. Further investigation needs to be done in order to fully understand the role of BclA proteins in C. difficile spores however, strong evidence suggest that these proteins are involved in the formation of the hair-like projections in most C. difficile strains such as the hyper-virulent strain R20291 [12,13] and their morphology and localization proposes them as potential antigens [14].…”
Section: Introductionmentioning
confidence: 99%
“…BclA3 is composed by an N-terminal domain, possibly oriented to the inside, a collagen-like domain formed by GXX repeats, which is highly glycosylated [10], and a C-terminal domain that is presumably faced outwards of the exosporium [17]. Mutant C. difficile spores lacking BclA3 have shown a reduced colonization efficiency in a mice infection model [16] and a recent study has shown that several glycosylated peptides from BclA3 were able to induce humoral immune response in mice [19].…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after, we used a gel-free proteomic method and a one-pot sample processing method that focused on the spore surface layers of B. cereus and C. difficile (22). Moreover, previous studies have described exosporium removal methods for C. difficile spores, and examined the exosporium protein components (23) as well as spore surface glycoproteins (24). Yet, none of these studies focusses on a comparative analysis that functionally links the spore and vegetative cell proteome.…”
Section: Introductionmentioning
confidence: 99%